Distribuiç\~ao de renda nos anos 2010: Uma década perdida para desigualdade e pobreza - Rogério J. Barbosa; Pedro H. G. Ferreira de Souza; Sergei Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– In this paper we analyze Pesquisa Nacional por Amostra de Domicílios Contínua (PNAD Contínua) microdata from 2012 to 2018 to document how the mid-decade economic recession reversed the trend of pro-poor growth that dated back to the early 2000s. Since the recession, there was a rise in inequality and poverty levels and aggregate welfare decreased. While average incomes surged from 2017 to 2018 they were still below their peak in 2014. More than 80% of all income growth between 2015 and 2018 accrued to the top 5%. Most distributional statistics suggest Brazil in 2018 was either back at the same levels or even worse-off than in 2012. This paper also relies on decomposition techniques to investigate the immediate causes behind this reversal of fortune. We find that the effects of the recession on the labor market explain a lot of the recent changes, but public transfers also played a role in distributional dynamics - either by action or inaction. Social assistance transfers and unemployment compensation failed to address rising inequality and poverty in any significant way. At the same time, Social Security contributed to surprisingly large increases in inequality due to the rise in pensions to the well-off. Finally, we show that in the past few years poverty rates were much more sensitive to changes in inequality than in average incomes. Indeed, if there were no increase inequality Brazil would have made further progress in reducing poverty even amid the recession.
Keywords: I3; I32; D31; I38; 330; Brazil; inequality; poverty; welfare; income; income transfer